Análise do nível de Alfabetização Científica de estudantes de escolas públicas de Bagé-RS - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This work deals with a study on Scientific Literacy, which aims to promote students' critical thinking in order to empower individuals to act in society in the best possible way, with the knowledge necessary to make decisions seen as appropriate involving culture, society and environment. Therefore, the problem question of this project is: What is the level of Scientific Literacy of third-year high school students in some public schools in the city of Bagé, Rio Grande do Sul? How does this result relate to the methodology and teaching resources used in your classes in the curricular components of the Natural Sciences area? To verify this level, the Simplified Basic Scientific Literacy Test will be used, which will be analyzed quantitatively, with anyone who achieves 60% correct answers in each of the three axes of the test being considered scientifically literate; To learn about the methodology and teaching resources, a questionnaire was prepared that will be analyzed qualitatively and quantitatively. Through this relationship, it was possible to observe that Traditional Education is present in the classes of students considered Scientifically Literate, however, it has factors that enhance Scientific Literacy. However, a possibility is proposed to improve the level of Scientific Literacy of students completing High School, based on the data collected, with the Research-based Teaching methodology.
Keywords: Alfabetização Científica; Ensino de Ciências; Ciências da Natureza; Ensino por Investigação; Scientific Literacy; Science teaching; Natural Sciences; Teaching by Research; CNPQ::CIENCIAS EXATAS E DA TERRA